Scientific Evidence Admissibility: Improving Judicial Proceedings to Decrease Erroneous Outcomes - Kwong, Leica (2019)
In the United States, Federal Rules of Evidence 702, the Frye and Daubert standards govern the admissibility of scientific evidence in the courtroom. Some states adopted Frye while others adopted Daubert, causing varying judicial outcomes. The verdicts in some cases may be erroneous due to a nationally used standard. Frye has broad criteria of requiring scientific evidence to be generally accepted. While Daubert contains more requirements for the evidence to be admissible, such as peer review, publication, and scientific principles. Daubert, alongside FRE 702, provides a thorough guideline for trial judges who have the gatekeeping role to decide admissibility aiming for reliable and relevant scientific evidence. To increase efficiency and validity in the court, use of Daubert and utilization of regular court appointed experts should be implemented in a new uniform standard across the United States